GSTP1 and GSTM3 Variant Alleles Affect Susceptibility and Severity of COVID-19 - Coric, Vesna; Milosevic, Ivana; Djukic, Tatjana; Bukumiric, Zoran; Savic-Radojevic, Ana; Matic, Marija; Jerotic, Djurdja; Todorovic, Nevena; Asanin, Milika; Ercegovac, Marko; Ranin, Jovan; Stevanovic, Goran; et al. (Frontiers in Molecular Biosciences, 2021)
Based on the premise that oxidative stress plays an important role in severe acute respiratory syndrome Corona virus (SARS-CoV-2) infection, we speculated that variations in antioxidant activities of different members of glutathione S-transferase family of enzymes might modulate individual susceptibility towards development of clinical manifestations in COVID-19. The distribution of polymorphisms in cytosolic glutathione S-transferases GSTA1, GSTM1, GSTM3, GSTP1 (rs1695 and rs1138272) and GSTT1 were assessed in 207 COVID-19 patients and 252 matched healthy individuals, emphasizing their individual and cumulative effect in disease development and severity. GST polymorphisms were determined by appropriate PCR methods. Among six GST polymorphisms analyzed in this study, GSTP1 rs1695 and GSTM3 were found to be associated with COVID-19. Indeed, the data obtained showed that individuals carrying variant GSTP1-Val allele exhibit lower odds of COVID-19 development (p=0.002), contrary to carriers of variant GSTM3-CC genotype which have higher odds for COVID-19 (p=0.024). Moreover, combined GSTP1 (rs1138272 and rs1695) and GSTM3 genotype exhibited cumulative risk regarding both COVID-19 occurrence and COVID-19 severity (p=0.001 and p=0.025, respectively). Further studies are needed to clarify the exact roles of specific glutathione S-transferases once the SARS-CoV-2 infection is initiated in the host cell.